The effects of mental games on third graders’ reading comprehension skills in Turkish classes - Yasemin Erdem; Bilge Gök (South African Journal of Education, 2022)
With the study reported on here we set about to reveal the effects of mental games on third graders’ reading comprehension skills in Turkish classes. The study group comprised 71 students, 35 of whom were included in the experimental group, and 36 in the control group. The experimental group played simple to difficult mental games selected by the researcher for 2 hours per week for 10 weeks. In the control group, the students continued with the traditional teaching process which excluded the playing of mental games until the end of the semester. Mental games like Whatzizz, detective, Q-bitz, Target 5, six, 3 stone, 9 stone, Skippity, Reversi, Kulami, that correspond to skills such as attention-concentration, reasoning, logical inference, and strategic thinking, were used. The study was conducted as a quasi-experimental pre-test/post-test control group design. The quantitative data were collected through the reading comprehension skill test. The pre-test data and the post-test-data collected through the test constituted the research data. The research data were analysed by using the 2-factor ANOVA test for mixed designs. The post-test scores of the students in the experimental group were higher than those of the students in the control group. The findings obtained from the quantitative analysis indicate that mental games had a positive effect on the Turkish reading comprehension of students in the experimental group as well as positive effects on students’ skills such as strategic thinking, logical inference and reasoning.